Safe Ride? Analysis of Female Consumer Behavior in the Context of Brazilian Ride-hailing - Violin, Fábio Luciano; Gouveia, Luis Borges; Zorzi, Mariciana; Arizaga, Hugo Ferreira (Cuadernos de Administración, 2026)
This study examines female consumption behavior in relation to ride-hailing services in Brazil, employing mixed methods to achieve a nationally representative sample. Findings emphasize the utilitarian and technological drivers of service use, which prevail over social and environmental considerations. Key factors such as physical violence, psychological violence, and self-preservation were found to be interdependent, leading to the development of an explanatory model of female consumption. While men and women share some foundational motivations for ride-hailing adoption, differences in the nature and timing of use generate distinct perceptions, shaping more flexible behavior among women. Environmental and social concerns remain secondary in decision-making; however, asymmetries related to violence and self-preservation become more pronounced during off-peak travel periods. Importantly, female consumption behavior is not static but varies according to contextual influences. These insights hold significant implications for future research and for organizations providing ride-hailing services, underscoring the necessity of adapting to the evolving needs of female users. This study establishes a benchmark in the analysis of female consumption behavior, challenging the notion of fixed determinants and highlighting the critical role of context and time of day in shaping decisions.